IMPLEMENTASI STRATEGI KOMUNIKASI PEMASARAN PT DBL INDONESIA PADA HONDA DBL DKI JAKARTA SERIES - Karimah, Dea Putri; Saputra, Windhi Tia; Wahyuningratna, Ratu Nadya (JURNAL PUSTAKA KOMUNIKASI, 2020)
Honda DBL has been held for 15 years in 30 cities in 22 provinces throughout Indonesia, including DKI Jakarta. In the implementation of the DKI Jakarta DKI DBL Series 2019, there was an increase of 30% participant participation and 77,229 viewers. The purpose of this research is to find out the implementation of PT DBL Indonesia's marketing communication strategy which was carried out at the DKI Jakarta Series Honda Developmental Basketball League (DBL) event. The researcher uses the concept of Integrated Marketing Communication (IMC) by Don Schultz as a tool to analyze the marketing communication strategies that are applied. This study uses descriptive qualitative methods to analyze and illustrate marketing communication strategies implemented by PT DBL Indonesia. Data collection techniques using interviews, observation and documentation. The results showed that an effective marketing communication strategy was implemented by PT DBL Indonesia, namely publications and public relations and word of mouth. This marketing communication strategy was applied at the Jakarta DBL Honda Series event. The published content will be discussed and form word of mouth among the public so that this event will be more widely known and participation will continue to increase again in the following years.